The Effect of Forecast Redundancy on Judgments of a Consensus Forecast's Expected Accuracy - Maines, Laureen A. (Journal of Accounting Research, 1990)
Laureen A. Maines, The Effect of Forecast Redundancy on Judgments of a Consensus Forecast's Expected Accuracy, Journal of Accounting Research, Vol. 28, Studies on Judgment Issues in Accounting and Auditing (1990), pp. 29-47